c.2 - "Nayyar, Deepak (ed.)" (Delhi, 1994)
The problems of industrialization in India, situated in the macro-economic perspective have been the subject of a lively debate in India. This volume brings together a selection of essays, published in the Economic and Political Weekly , that made a significant contribution to the debate. This book is intended for economists, students of development economics, policy planners.
Keywords: Industrial growth